2016
DOI: 10.1007/s11262-016-1303-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel reassortant H1N2 influenza virus containing genes from the 2009 pandemic human H1N1 virus in swine from eastern China

Abstract: Pandemic outbreaks of H1N1 swine influenza virus have been reported since 2009. Reassortant H1N2 viruses that contain genes from the pandemic H1N1 virus have been isolated in Italy and the United States. However, there is limited information regarding the molecular characteristics of reassortant H1N2 swine influenza viruses in eastern China. Active influenza surveillance programs in Zhejiang Province identified a novel H1N2 influenza virus isolated from pigs displaying clinical signs of influenza virus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Risk for possible emergence of zoonotic strains has been demonstrated worldwide. H1N2 viruses isolated from pigs in China replicated efficiently in mice and pigs ( 32 , 36 , 37 ), while viruses from South Korea and Europe transmitted to and even caused death in ferrets ( 33 , 34 , 38 ). Future work will focus on how these reassortants arose in Chile BPFs and the role of specific genetic differences in pathogenicity and transmissibility.…”
Section: Discussionmentioning
confidence: 99%
“…Risk for possible emergence of zoonotic strains has been demonstrated worldwide. H1N2 viruses isolated from pigs in China replicated efficiently in mice and pigs ( 32 , 36 , 37 ), while viruses from South Korea and Europe transmitted to and even caused death in ferrets ( 33 , 34 , 38 ). Future work will focus on how these reassortants arose in Chile BPFs and the role of specific genetic differences in pathogenicity and transmissibility.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic reassortment between enzootic swine and pH1N1 strains giving rise to H1N2 virus diversification has also been reported in Asia, including lineages in South Korea containing Eurasian avianlike swine HA and Korean swine H1N2 NA gene segments and the pH1N1-like internal gene cassette (21) and another reassortant strain associated with pig respiratory disease in China incorporating the HA, basic polymerase protein 2, and M genes of swine pH1N1 virus origin; the remaining gene segments were derived from a swine H3N2 strain (22).…”
Section: Interspecies Transmission Of Reassortant Swine Influenza a Vmentioning
confidence: 98%
“…A few studies have reported reverse-transcription PCR based amplification of all the eight gene segments of IAV to generate the whole genome sequences [33,91,128,231] but in most cases, the whole genome sequences were generated using MiSeq next-generation sequencing approach [150,214,325,329]. A great advantage of this sequencing approach is that it can identify novel influenza viruses in the swine samples [80,90,301].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a novel strain of avian-origin H4N1 virus was isolated from a Chinese swine in 2009 [80]. Several classical and avian-like H1N1, Eurasian avian-like H1N1, triple-reassortant H1N1, H1N2, H3N2 and A(H1N1)pdm09 viruses were reported in Chinese swine between 2009 and 2016 [81][82][83][84][85][86][87][88][89][90][91]. A triple-reassortant H1N1 virus having the internal genes of avian, human, and swine lineages of influenza viruses was reported from a two-month old piglet on a Guangdong based swine farm in January 2010 [92].…”
Section: Chinamentioning
confidence: 99%